Representasi Maskulinitas pada Tokoh Gay Sarawat dalam Serial Film 2gether: The Series (E-Jurnal Medium, 2022)
The concepts of sex and gender have different understandings. However, the existing social construction emphasizes that the ideal gender behavior is in accordance with sex identity, namely that men must be masculine and women must be feminine and must like the opposite sex. Various stereotypes then emerged for homosexuals, one of it was gay who did not have masculinity. This study aims to describe the problem through the character of Sarawat in 2gether: The Series through a qualitative approach. This study uses Roland Barthes' semiotic analysis to examine the meaning of denotation and connotation and then it will be associated with the myth of masculinity which refers to the characteristics of masculinity based on David and Brannon with Beynon. The results of this study are in the form of several categories of representation of masculinity according to David and Brannon with Beynon on the characters of Sarawat, such as no sissy stuff (not girls), be a big wheel (get admiration from others), give 'em hell (aggressive and brave), be a sturdy oak (able to hide emotions), new lad (macho and build a life around football), and metrosexual. In addition, the character Sarawat is sexually oriented gay king, so it can be said that this film series tries to provide new knowledge about the various genders that exist in Thailand.